Analisis Mutu Layanan Kesehatan (Tangible, Realibility) Terhadap Tingkat Kepuasan Kunjungan Ibu Hamil TM I Di Puskesmas Labuhan Deli Kecamatan Labuhan Deli Kabupaten Deli Serdang Tahun 2023 - Sonia Novita Sari; Noni Handayani Br Tarigan; Nur Azizah; Rosmani Sinaga (Jurnal Ventilator, 2023)
Antenatal care is care or care provided to pregnant women before birth, which is useful for facilitating healthy and positive outcomes for pregnant women. Perfect health services have an impact on the quality of service that gives satisfaction to everyone. This study aims to determine the relationship between the quality of health services (tangible, reliability) to the level of satisfaction of the visit of TM I pregnant women at the Labuhan Deli Health Center, Labuhan Deli District, Deli Serdang Regency. This research is an analytical quantitative research using a cross sectional design. The population in this study were all TM I pregnant women who visited the Labuhan Deli Health Center, namely 56 respondents at the Labuhan Deli Health Center, Labuhan Deli District, Deli Serdang Regency in 2023. The sampling technique was accidental sampling. Data collection was analyzed by chi-square test. The results of this study indicate that there is a correlation between the satisfaction of pregnant women at the Labuhan Deli Health Center, Labuhan Deli District, Deli Serdang Regency in 2023 based on the tangible dimension (physical evidence), and there is no relationship between the level of satisfaction of pregnant women at the Labuhan Deli Health Center, Labuhan Deli District, Deli Serdang Regency in 2023 based on dimension of realibility (reliability).